Investigating the shared genetic architecture between schizophrenia and sex hormone traits - Xiaoyan He; Qingyan Ma; Jing Liu; Pu Lei; Huan Peng; Wen Lu; Yixin Liu; Xianyan Zhan; Bin Yan; Xiancang Ma; Jian Yang (Translational Psychiatry)
Abstract Sex hormones are involved in schizophrenia pathogenesis; however, their direction and genetic overlap remain unknown. By leveraging summary statistics from large-scale genome-wide association studies, we quantified the shared genetic architecture between schizophrenia and four sex hormone traits. Linkage disequilibrium score regression and bivariate causal mixture modeling strategies showed significant positive correlations between sex hormone-binding globulin (SHBG), total testosterone, and schizophrenia, while bioavailable testosterone and schizophrenia were negatively correlated. Estradiol showed a weak positive correlation with schizophrenia, with little polygenic overlap. The conjunctional false discovery rate method identified 303 lead single-nucleotide polymorphisms (SNPs) in jointly shared genomic loci between schizophrenia and SHBG, with 130, 52, and 9 SNPs shared between schizophrenia and total testosterone, bioavailable testosterone, and estradiol, respectively. Functional annotation suggests that mitotic sister chromatid segregation and N-glycan biosynthesis may be involved in common mechanisms underlying sex hormone regulation and schizophrenia onset. In conclusion, this study clarified the inherent relationships between schizophrenia and sex hormone traits, highlighted the roles of mitotic sister chromatid segregation and N-glycan biosynthesis in the pathogenesis of schizophrenia, and delivered potential targets for further validation.